International corporate investment and the relationships between financial constraint measures - Cleary, Sean (Journal of Banking & Finance, 2006)
This paper uses international panel data to examine the interrelationships among some commonly used measures of financial constraint. The analysis reveals the following insights: (1) firms with stronger financial positions are more investment-cash flow sensitive than firms with weaker financial positions even after controlling for size and dividend payout and (2) higher payout firms are more investment-cash flow sensitive than lower payout firms even after controlling for size and financial strength. Evidence regarding the impact of firm size that is documented originally becomes much weaker once financial health and dividend payout behavior are controlled for. Finally, additional analysis reveals that many of these results may be driven by the fact that firms possessing high cash flow volatility display lower investment-cash flow sensitivities.